Rights of youth in european charter on the participation of young people in local and regional life - Voitovich, P. P.; Войтович, П. П.; Войтовіч, П. П. (Одеса : Фенікс, 2014)
European Charter on the Participation of Young People in Local and Regional Life is very important document in the sphere of rights of youth. However it contains only general provision and has a recommendatory character. So, it has to be further implemented into national legislation.
Voitovich, P. P. Rights of youth in european charter on the participation of young people in local and regional life / P. P. Voitovich // Правове життя сучасної України: матеріали Міжнар. наук. конф. проф.-викл. та аспірант. складу / відп. за вип. В. М. Дрьомін; НУ ОЮА, Півд. регіон. центр НАПрН України. – Одеса: Фенікс, 2014. – Т. 2. – С. 290-292.
Keywords: rights of youth in european charter on the participation of young people in local and regional life; Права молодежи в Европейской хартии об участии молодежи в местной и региональной жизни; права молоді у Європейській хартії про участь молоді в місцевому і регіональноми житті